RequirementX: um a ferramenta para suporte à gerência de requisitos em extreme Programming baseada em mapas conceituais - Martins, Júnior Machado (Universidade do Vale do Rio do Sinos, 2007)
One of the hardest tasks of building a software system is requirements elicitation, which triggers a knowledge discovery action. Thus, many techniques are used with the intention to minimize idea conflicts, misformed concepts, erroneous interpretations and missing data; In order to achieve this goal, scenarios interviews, User Stories, viewpoints and Use Case diagrams are techniques to reduce the distance between the researcher and the user on requirement elicitation. Concept maps have been used as efficient way to represent knowledge. This research uses concept maps to deal with the organization, identification and improvement of concepts and software requirements definitions in a cooperative way, making use of the User Story format introduced by the Extreme Programming (XP) methodology. The proposed process is supported by a web-based tool, which automates the generation, organization and management of the requirements capture generated in the Concept Maps format
Keywords: algoritmo genético; aprendizagem; computação; máquina; rede neural artificial; robótica móvel autônoma; UML-MC; cmaptools; conceptual maps; ontology; OWL; RDF; UML; user story; XML; XP; extreme programming; semantic WEB; Ciências Exatas e da Terra